2018
DOI: 10.3329/bjms.v17i2.35877
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study to elucidate the effects of Septilin TM on immune pathways

Abstract: Objective: The use of herbal immunomodulatory preparations to prevent and treat immunological complications is increasing in popularity. Rigorous in vitro, in vivo and clinical trial studies are needed to ensure safety, quality and efficacy for the wellbeing of patients. SeptilinTM, a proprietary herbal medicinal product has been reported to have immunomodulatory effects. This study investigated the in vitro effects of SeptilinTM on biomarkers of specific immune pathways by using whole blood culture assays (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
2
3
0
Order By: Relevance
“…Similar findings of increased anti-inflammatory cytokine (IL-10), pro-inflammatory cytokines (IL-1α, IL-1β, TNF-α), and chemokine production were observed in PBMCs treated with the combination of PHA and PN water extracts. This study strengthens evidence that PN can illicit increased production of MIP1-β, IL-1α, and IL-1β after treatment with traditional medicine as previous shown with other traditional medicines ( Barak et al, 2002 ; Denzler et al, 2010 ; Hoosen and Pool, 2018 ). Pro-inflammatory cytokines like TNF-α, IL-1α, IL-1β, and chemokine MIP1-β have been implicated in multiple immunopathological conditions ( Sandeep Varma et al, 2011 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings of increased anti-inflammatory cytokine (IL-10), pro-inflammatory cytokines (IL-1α, IL-1β, TNF-α), and chemokine production were observed in PBMCs treated with the combination of PHA and PN water extracts. This study strengthens evidence that PN can illicit increased production of MIP1-β, IL-1α, and IL-1β after treatment with traditional medicine as previous shown with other traditional medicines ( Barak et al, 2002 ; Denzler et al, 2010 ; Hoosen and Pool, 2018 ). Pro-inflammatory cytokines like TNF-α, IL-1α, IL-1β, and chemokine MIP1-β have been implicated in multiple immunopathological conditions ( Sandeep Varma et al, 2011 ).…”
Section: Discussionsupporting
confidence: 89%
“…Candidates of the study were also assessed regarding medicinal plants utilization against day to day issues and diseases. The outcome of the current survey showed that majority of the participants were using medicinal plants to treat many ailments and previous studies also supported this investigation as medicinal plants are enriched source of phytochemicals that have potential therapeutic activities to cure diseases 37,38 . However, many of the effects of medicinal plants are not completely understood, yet found effective as therapeutic agents and still there is a need to conduct more research in this area of study 39,40 .…”
Section: Figure 6 Responses Among Universities About Commonly Use Med...supporting
confidence: 66%
“…Table III 25 stated that green tea extract with a concentration of 20% in its flavonoid content had activity as a tyrosinase inhibitor so that it would prevent the formation of melanin due to UV-B rays, polyphenols in green tea could function to protect the skin from UV radiation and inhibit the process melanogenesis so that the increase in the amount of melanin was inhibited and the tannin content in green tea could function as a lightener with an anti-tyrosinase mechanism so that melanin production could be inhibited. The results of this study lacked effectiveness as a lightening agent [26][27][28] . Limitations and shortcomings in this study were the activities of respondents who were exposed to sunlight so that it could inhibit the work of epigallocatechin gallate lightening cream and the inhibition of the malagonesis process was less than optimal.…”
Section: Paired Samples Test Nilai P Keteranganmentioning
confidence: 74%